Nursing care in patients with cardiotoxicity induced by chemotherapy (Research, Society and Development, 2021)
Cardiotoxicity induced using chemotherapeutic agents can generate devastating cardiac problems worse than cancer, in addition to hindering the patient's treatment and prognosis. This study aimed to describe the risk factors for cardiotoxicity by chemotherapy and, more specifically, to describe nursing care for patients who had cardiotoxicity due to chemotherapy and radiation therapy. The research is a bibliographic review with a descriptive and qualitative approach. A search was performed in the Google Scholar Databases, VHL (virtual health library) and SciELO (Scientific Electronic Library Online), which resulted in a final sample of 24 articles. After the analysis, it was possible to identify that the main risk factors for developing cardiotoxicity are age over 60 years, hypertension, heart disease and use of chest radiotherapy. But anticyclic antineoplastic agents and trastuzumab, anthracyclines, alkylating agents, monoclonal antibodies, and tyrosine kinase inhibitors are triggers of cardiotoxicity, the moment these chemotherapies are used in the treatment of cancer it is necessary to carry out an assessment of cardiac function before and after administration of this chemotherapy. There is a possibility that such drugs may cause heart failure, ischemia, arrhythmia, peri-cardiopathies, among other problems if cardiotoxicity occurs. The main nursing care in chemotherapy-induced cardiotoxicity are checking vital signs, weight, and height; evaluate the results of exams; notify the doctor about complications; intervene immediately in the occurrence of possible side effects during medication.